(untitled) (Journal of Educational Sciences, 2017)
The results of studies (2003-2016) was devoted to the modern form of existence of music, which is the socio-cultural and educational environment for the modern student – e-music. It refers to music with those characteristics of the activity (in the process of its creation, perception, etc.),which imposes on it the computerization of the data fields (represented musically-computer technology). The application of humanitarian and holistic approach, methods of synthesis and the systemic and holistic analysis shows the arguments of the relevance and potential use by students of emusic in various directions of self-realization. Summed up, including conclusions about the need for the study in the context of this qustion the following problems: the principles of education, risk, artistic repertoire, etc. E-music is (by its digital nature) may be part of a high-tech information educational environment and should be involved in it, as she (being the electronic form of music itself) performs the role of cultural and educational, social and cultural environment of our contemporary.